2017
DOI: 10.7150/thno.19979
|View full text |Cite
|
Sign up to set email alerts
|

Direct Macromolecular Drug Delivery to Cerebral Ischemia Area using Neutrophil-Mediated Nanoparticles

Abstract: Delivery of macromolecular drugs to the brain is impeded by the blood brain barrier. The recruitment of leukocytes to lesions in the brain, a typical feature of neuroinflammation response which occurs in cerebral ischemia, offers a unique opportunity to deliver drugs to inflammation sites in the brain. In the present study, cross-linked dendrigraft poly-L-lysine (DGL) nanoparticles containing cis-aconitic anhydride-modified catalase and modified with PGP, an endogenous tripeptide that acts as a ligand with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
106
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(106 citation statements)
references
References 50 publications
0
106
0
Order By: Relevance
“…Due to early neutrophil infiltration into ischaemic brain tissues, neutrophils were considered as cargo vehicles to deliver macromolecular drugs to block reactive oxygen species‐mediated apoptosis following stroke . Clinical studies demonstrated that the neutrophil‐to‐lymphocyte ratio might be a strong prognostic marker in acute ischaemic stroke and that neutrophil extracellular traps are increased in patients with stroke .…”
Section: Myeloid Cells From the Periphery Respond To Stress Signals Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to early neutrophil infiltration into ischaemic brain tissues, neutrophils were considered as cargo vehicles to deliver macromolecular drugs to block reactive oxygen species‐mediated apoptosis following stroke . Clinical studies demonstrated that the neutrophil‐to‐lymphocyte ratio might be a strong prognostic marker in acute ischaemic stroke and that neutrophil extracellular traps are increased in patients with stroke .…”
Section: Myeloid Cells From the Periphery Respond To Stress Signals Rmentioning
confidence: 99%
“…62 Due to early neutrophil infiltration into ischaemic brain tissues, neutrophils were considered as cargo vehicles to deliver macromolecular drugs to block reactive oxygen species-mediated apoptosis following stroke. 63 Clinical studies demonstrated that the neutrophil-to-lymphocyte ratio might be a strong prognostic marker in acute ischaemic stroke 64 and that neutrophil extracellular traps are increased in patients with stroke. 65 Neutrophil extracellular traps are produced by activated myeloid cells, including neutrophils, as networks of DNA, histones and proteolytic enzymes, and are capable of activating platelets and contribute to the thrombotic processes.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of cerebral ischemia is closely linked to cerebral arteriosclerosis (Moroni et al, ), and chronic cerebral insufficiency is the most likely cause of dizziness, sleep disorders, and memory loss (Chen, Du, Xu, Liu, & Wang, ; Scheidt et al, ). Drug and operation are currently the cardinal treatments for cerebral ischemia (Powers et al, ; Zhang et al, ). Some patients with cerebral ischemia are curable; however, some patients require lifelong medication.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most used biomaterial‐based nanostructures in the combinational studies are the polymeric ones. These nanostructures find several uses as supportive scaffolds for the delivery of MSCs, as nanoparticles for drug and gene delivery or as coatings for inorganic nanoparticles . Each of these nanostructures is able to encapsulate a variety of therapeutics, including antioxidants such as catalase,86a nanoceria, and edaravone, growth factors such as VEGF, and other neuroprotectants such as glyburide86b and the NR2B9C therapeutic peptide 86c.…”
Section: Combinational Approachesmentioning
confidence: 99%